The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1051/0004-6361:20053532
|View full text |Cite
|
Sign up to set email alerts
|

The extent of 3-min oscillations in regions other than sunspot plumes

Abstract: The active region, AR0554, was observed with NIS/CDS on board SoHO to examine the extent and range of oscillations from a range of features. Among all the NIS spectral lines analysed, significant oscillations were found in Si xii 520 Å, Mg x 625 Å, O v 629 Å, and He i 522 Å. The periods of the strongest oscillations in these lines were ≈10−20 min. After the dominant 10−20 min oscillations were filtered out from these lines, only O v 629 Å showed significant (i.e. above the 95% significance level) shorter-perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Figure 7 demonstrates such an example: the P700-filtered wavelet spectrum shows that there are only two major period bands, 200-300 s and 400-500 s, for the oscillations before 30 min while the spectrum of the oscillations between 30 and 60 min extends from 100 s to 700 s. When the modes of periods longer than 300 s are filtered out, the strongest oscillation in the P300-filtered signal often shows a periodicity ≈3 min, and the oscillation is most significant for the time interval 30-65 min of the observing sequence, which corresponds to the transit time interval for the MMF across our CDS pixel. This result echoes the conclusion by Lin et al (2005) that 3-min oscillations can exist outside of a sunspot in regions with strong magnetic fields.…”
Section: Oscillationssupporting
confidence: 90%
“…Figure 7 demonstrates such an example: the P700-filtered wavelet spectrum shows that there are only two major period bands, 200-300 s and 400-500 s, for the oscillations before 30 min while the spectrum of the oscillations between 30 and 60 min extends from 100 s to 700 s. When the modes of periods longer than 300 s are filtered out, the strongest oscillation in the P300-filtered signal often shows a periodicity ≈3 min, and the oscillation is most significant for the time interval 30-65 min of the observing sequence, which corresponds to the transit time interval for the MMF across our CDS pixel. This result echoes the conclusion by Lin et al (2005) that 3-min oscillations can exist outside of a sunspot in regions with strong magnetic fields.…”
Section: Oscillationssupporting
confidence: 90%
“…Indeed, the strong magnetic field regions (sunspots, magnetic network cores) show predominantly 3-min oscillations in the chromosphere. Note that some observations also show the 3-min oscillations in the solar corona above sunspots (De Moortel et al 2002) and other magnetic structures (Lin et al 2005). These oscillations can be excited as a consequence of consecutive shocks due to chromospheric 3-min oscillations.…”
Section: Discussion and Summarymentioning
confidence: 86%
“…Propagating acoustic waves are frequently seen in the solar corona as periodic variations of spectral line intensity (De Moortel et al 2000, Marsh et al 2003, Lin et al 2005, 2006, Srivastava et al 2008, Wang et al 2009. As these waves are often observed within the frequency range corresponding to the acoustic waves in the solar photosphere/chromosphere, this logically leads to the idea of penetration of the photospheric acoustic oscillations into the corona.…”
Section: Introductionmentioning
confidence: 99%
“…Tsiropoula et al (2009) reported 5 min oscillations in the dark mottle and network boundaries, and suggested the upward propagating waves at the network boundary, and standing waves at the mottle region. In the previous studies, 3 min oscillations are widely reported in the TR spectral line formed above the sunspots, and interpreted as a signature of upward propagating waves (e.g., Gurman et al 1982;Brynildsen et al 1999;Maltby et al 2001;Fludra 2001;O'Shea et al 2002;Brynildsen et al 2003Brynildsen et al , 2004Lin et al 2005;Sych et al 2012). Jess et al (2008) studied the velocity oscillations in the bright active region at the TR height and reported high frequency oscillations with a dominant period of 26 ± 4 sec.…”
Section: Introductionmentioning
confidence: 95%